Application of Google cloud computing for web-based library information systems at Bahayangkara University Surabaya - Irsyadi, Muhammad Haidir; Alam, Fajar Indra Nur; Sari, Anggraini Puspita; Agussalim, Agussalim (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
Libraries are essential in academic work as they expose people to structured, easily procurable information.  However, the majority of schools, including Bhayangkara University Surabaya, still face challenges in managing and storing library information because local or manual systems are substandard. The goal of this project is to deploy and test the effectiveness of Google Cloud Computing technologies, such as Google Cloud Storage, Google Cloud SQL, and Google Compute Engine, on a website-based library information system.  We adopted a quantitative approach by performing experiments and system testing, i.e., black-box testing, access speed testing, and heavy load resistance testing. The result of the implementation is massive benefits, including a response time of 2 seconds on average, stability with 500 users at the same time, and storage efficiency at just 30% of the original size.  Other colleges can have an example that they can use to make a change to a cloud-based digital library from this research.  This also helps create digital library information systems that are technology-centered and dependable.